Management of Hypertensive Disorders in Pregnancy- An Update (Bangladesh Journal of Obstetrics & Gynaecology, 2013)
Hypertensive disorder is the most common medical problem encountered in pregnancy with a high perinatal and maternal mortality & morbidity. According to the onset of hypertension in relation to pregnancy and its duration and the development of proteinuria & convulsion it is   categorized into several types. The prognosis depends on duration and severity of hypertension and multi-system involvement. Aim of management is to achieve a gradual and sustained lowering of BP to prevent maternal complications and to allow prolongation of pregnancy for fetal benefit. For management purpose, according to recent NICE clinical guideline gestational hypertension has been classified into mild, moderate and severe hypertension. Till now there is controversy regarding the use of antihypertensives in mild to moderate hypertension. Labetalol, hydralazine & methyldopa are used as first line drugs according to severity of hypertension. Magnesium sulphate is the anticonvulsant of choice and nimodipine is the newer alternative. Obstetric management in all the types of hypertensive disorders is almost same .Expectant management can be considered for women at